Production of Poly Lactic Glycolic Acid from Solid Waste of Palm Starch Industry for Applications in the Field of Medical Biomaterials - Purnavita, Sari; Rahayu, Lucia Hermawati; Rinihapsari, Elisa (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract Palm starch industry bring out solid waste that contain high total cellulose (cellulose and hemicellulose), that is 82,03%. Cellulose from solid waste of palm starch industry can be used in lactic acid production through hydrolysis and fermentation processes. Enzymatic hydrolysis and fermentation processes will work efficient and effectively when run simultaneously in one reactor, known as Simultaneous Sacharificatian and Fermentation (SSF). This research aimed to find out the most effective pH and quantity of inoculum in SSF process. This research was using substrate from solid waste of palm starch industry that treated by delignification using NaOH 7% and then saccharificated and fermented simultaneously using enzyme from Trichodermareesei for saccharification process, and Lactobacillus delbrueckii bacteria FNCC 0045 for lactic acid fermentation. The research was held by pH variation of 4, 5, 6 and 7, while quantity of inoculum were 5, 10, 15, 20 and 25% respectively. The incubation was at 46°C for 96 hour. The result showed that optimal pH was 6 and 25% inoculum was the best. Production of PLGA films was started with the polymerization reaction between lactic acid and glycolic acid at various ratios of monomer (wt%) = 95:5 and PLGA :PVA at various ratio (wt%)= 3:2, 3:3, 3:4, 3:5.The solution of PLGA in chloroform was added with PVA solution (as the film forming agents) and aloe vera gel (as an anti-microbial agents) subsequently, and then stirred with a magnetic stirrer for about 10 minutes until homogeneous. The homogeneous PLGA solution thereafter poured on the mold (glass plate). The results showed that the greater the amount of poly vinyl alcohol (ratio 3:5 % by weight), the greater the tensile strength of the film, but the lower elongation. Keywords: solid waste of palm starch industry; lactic acid; SSF;PLGA